Influence of weather variables on spore biology of Corynespora cassiicola, an incitant of target leaf spot disease of tomato. (7th February 2020) - Dutta, S.; Kamei, A.; Goldar, S.; Datta, G.; Bharati, D. R. S.; Ghorai, A. K.; Pathak, S.; Roy Barman, A.; Jash, S.; Ray, S. K.
Abstract: Among the various biotic and abiotic factors limiting production of tomato, target leaf spot disease caused by Corynespora cassiicola has been emerged as a serious problem in vegetable based cropping systems. In the current research work, the influence of varying environmental conditions including temperature, light, and relative humidity on conidial germination (CG), germ tube elongation (GTE) and sporulation (SP) of C. cassiicola was studied under controlled conditions. The temperature of 25 °C was most congenial for CG and GTE both under light and darkness conditions. The temperature range of 25 °C–30 °C was optimum for CG. Conidial germination increased progressively from 15 to 25 °C both under light and dark conditions and decreased with further increase in temperature. High rate of CG was observed under continuous darkness in comparison to continuous light irrespective of temperature. Lesser duration of light had a stimulatory influence on SP of C. cassiicola and 10 h light/14 h dark cycle at 25 °C temperature was most optimum for SP. Relative humidity (RH) at 95% was optimum for CG, GTE and SP and thus, justified the peak occurrence of the target leaf spot disease during 50-4 Standard meteorological week (SMW). Comparatively higher level of CG was obtained at the humidity range of 95%–100% with the best at 100% RH (92.6%). Increasing humidity significantly decreased the time of spore production. Maximum time required for spore production (69.2 h) was observed at 85% RH followed by 95% RH (50.2 h).